Qualitative Dimensions of Educational Spaces: Interpretation Possibilities – Theory and Practice (Training and Practice : Journal of Educational Sciences, 2012)
For social and cultural studies, space constitutes the subject of research as a social creation, by which we can shade our concepts of culture and identity. At all times, space can be conceptualised through the cultural meanings associated with it. Basic forms of its division – villages, cities, regions or nation states – are the result of cultural systems, which on one hand create concepts, and on the other hand create consensus about the meanings determined by them.How does the concept of space appear and how can it be interpreted in the auxiliary disciplines of education?In my paper, following the anthropological and sociological interpretations of space, I will present the qualitative dimensions of educational spaces based on architectural space-types. Finally, I will point out the practical importance of the qualitative dimensions of school spaces.